Gender equity in academic rheumatology, current status and potential for improvement: a cross-sectional study to inform an EULAR task force. Issue 2 (8th August 2022) - Ovseiko, Pavel V; Gossec, Laure; Andreoli, Laura; Kiltz, Uta; van Mens, Leonieke; Hassan, Neelam; van der Leeden, Marike; Siddle, Heidi J; Alunno, Alessia; McInnes, Iain B; Damjanov, Nemanja S; Apparailly, Florence; et al.
Abstract : Objectives: Evidence on the current status of gender equity in academic rheumatology in Europe and potential for its improvement is limited. The EULAR convened a task force to obtain empirical evidence on the potential unmet need for support of female rheumatologists, health professionals and non-clinical scientists in academic rheumatology. Methods: This cross-sectional study comprised three web-based surveys conducted in 2020 among: (1) EULAR scientific member society leaders, (2) EULAR and Emerging EULAR Network (EMEUNET) members and (3) EULAR Council members. Statistics were descriptive with significance testing for male/female responses assessed by χ 2 test and t-test. Results: Data from EULAR scientific member societies in 13 countries indicated that there were disproportionately fewer women in academic rheumatology than in clinical rheumatology, and they tended to be under-represented in senior academic roles. From 324 responses of EULAR and EMEUNET members (24 countries), we detected no gender differences in leadership aspirations, self-efficacy in career advancement and work–life integration as well as the share of time spent on research, but there were gender differences in working hours and the levels of perceived gender discrimination and sexual harassment. There were gender differences in the ranking of 7 of 26 factors impacting career advancement and of 8 of 24 potential interventions to aid career advancement. Conclusions: There are gender differences in career advancement in academic rheumatology. The study informs a EULAR task force developing a framework of potential interventions to accelerate gender-equitable career advancement in academic rheumatology.